2020
DOI: 10.3126/ijasbt.v8i2.28325
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Plants of Tharu Community of Eastern Nepal

Abstract: Ethnobotany is the study of ethnic plants of particular people living in particular place. It accommodates list, details and description of all those studied plants regarding with their various uses. Tharu people belong to one of the indigenous communities especially in Terai region of Nepal. Tharu people have been using these plant resources since 18th century. This study aims to identify ethnic plants of Tharu community of eastern Nepal and their uses in their daily lives.  Enumeration of useful plants from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 18 publications
8
13
0
Order By: Relevance
“…This might be due to the easy availability of the leaves and as a major part of nutrients synthesis and thus higher biochemical activity. The dominance of leaf as a plant part in the present study has been supported by Chaudhary et al [5], Acharya and Acharya [22], Singh [23]. The documented 107 species plants are used in the treatment of 39 different diseases and 46 distinct health benefits activities.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…This might be due to the easy availability of the leaves and as a major part of nutrients synthesis and thus higher biochemical activity. The dominance of leaf as a plant part in the present study has been supported by Chaudhary et al [5], Acharya and Acharya [22], Singh [23]. The documented 107 species plants are used in the treatment of 39 different diseases and 46 distinct health benefits activities.…”
Section: Discussionsupporting
confidence: 66%
“…This might be due to the modernization and easy availability of chemically synthetic drugs in medical shops. Chaudhary et al [5] have also reported a similar difference in age groups of the respondent while studying the ethnobotanical plant of Tharu community of eastern…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations